(untitled) (Reflection and Critique Law Magazine, 2020)
The present study aims to address a critical analysis on the historical and critical trajectory of the theories of linking fundamental rights in the Democratic Rule of Law (vertical, horizontal and diagonal effectiveness of fundamental rights), presenting their historical context, their foundations, their main criticisms, their effects. and its applicability, still discussing, at its end, the points of tension and confluences in the modern theory of diagonal efficacy. The development of the study will still have to be observed under the following paradigm of question: would this be an independent theory? Or: Is this just a branch of horizontal effectiveness theory? It will seek to define and understand under the analysis of the doctrines applicable to the proposed problem. The studies presented here were prepared considering the perspectives of the Democratic Rule of Law and the liberal and communitarian policies. We can also observe the historical course of such theories and how they fit into their respective historical moments.